As used on the famous Nelson Mandela underground adventures in the arms and torture trade - Thomas, Mark (Ebury, 2007)
Provides an account of Mark's rampage through the arms trade. This book describes an industry fraught with loopholes, complacency and greed; that allows corrupt regimes to kill, maim and displace, but whose deals are often subsidised by the British taxpayer.